Comparative analysis of different materials to be used for backfilling in underground mine voids with a particular reference to hydraulic stowing. (2017) - Gupta, Anup Kumar; Paul, Biswajit
A comparative analysis was performed between different materials like sand, pond ash, fly ash and OB with parameters such as grain size distribution, porosity, percolation, permeability, water holding capacity, bulk density and specific gravity to assess their suitability as a filling material in underground mine voids. All the parameters stated above have their direct or indirect effects on drainage property which is a key factor in hydraulic stowing (to achieve a stable packing). Grain size analysis result confirmed the sandy nature of OB with about 70% of sand size particles that is a good sign for its resemblance with natural sand and thus possible alternative of sand as a filling material. Other parameters like permeability, porosity and percolation was also found more or less similar to sand and better than other two materials. [Received: November 3, 2015; Accepted: March 10, 2016]